PERFORMANCE FIELD EVALUATION OF DRIP IRRIGATION SYSTEMS UNDER CONDITIONS OF THE DESERT REGION IN WESTERN IRAQ - & et al., Al-Mehmdy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
A field experiment was carried out at Al-Saqlawiya township Al-Anbar governorate at north in latitude 33°24´57"  and east longitude 43°41´23", during period from 15/10/2018 to 15/1/2019 in order to evaluate the performance of  5 units of surface drip irrigation system, components and periods of use, by the steps recommended by the American Agriculture Engineers Association, at 50 kPa operational pressure. Results showed that there was a disparity in values of emitters actual discharge, uniformity coefficient, emission uniformity and variation percent of discharge. Although the similarity of most measurement conditions such as land area, design, management and the operational pressure except of the periods of using these systems which ranged 2-5 years. The decrease percent of actual discharge values 8.06%, 8.74%, and 19.04% when comparing the actual discharge for the system 1 with the values of systems 2,3 and 4, respectively. While the increase percent of the actual discharge value reached 29.74% when comparing of system 1 with system 5. Uniformity coefficient of system decreased were 5.32%, 19.95%, 3.81% and 7.21%, respectively, and 10.73%,37.25%,7.51% and 14.36% for the decrease percent of emission uniformity comparing the system 1 with the systems 2, 3, 4 and 5, respectively, as for the increase percent for the variation emitters discharge, it were 7.70%, 118.73%, 7.70%, respectively. Non- compliance of users of these systems with regular maintenance of the end of agriculture seasons, poor storage conditions, not maintained at high temperature or cold conditions and increase use periods, all had caused the expansion of emitters' holes, which affected negatively in some values of the followed evaluation standard.